Self-image, self-acceptance and the therapeutic effects among patients suffering from mental and physical diseases – comparative study - Zboralski, Krzysztof; Gałecki, Piotr; Orzechowska, Agata; Berent, Dominika; Talarowska, Monika (Current Problems of Psychiatry, 2011)
Aim: The aim of the study is to get to know about mutual relationships between individual self-imagine, level of self-acceptance and the therapeutic effects among patients who suffer from mental diseases and physical diseases. Material and methods: The study involved 97 people, divided into two groups: 41 patients with recurrent depressive disorder (first group) and 56 people treated for selected somatic disorders (gastrointestinal diseases, skin diseases and diabetes type 1 and type 2 – the second group). The personal questionnaire, Adjective Check List by H.G. Gough and A. B. Heilbrun (ACL) and Clinical Global Impression Scale (CGI) were used in the examination. Results: Statistically significant relationships between the analyzed variables were observed. The size of therapeutic effect is associated with the level of self-acceptance, and with positive self-image of the patients. Patients with higher levels of self-acceptance achieved greater improvement as a result of the treatment. Using this relationship applies to both patients somatically and mentally ill. Conclusions: • The size of therapeutic effect is associated with the level of self-acceptance and with the self-image of the patients. • Patients with higher levels of self-acceptance achieved greater improvement in the assessment of the treatment. • Using this relationship applied to both patients somatically and mentally ill. • Between patients with depression and somatic illness differences mainly concerned the current image, but there was a very similar ideal self-image.